Hanging in there: Zimbabwean migrant workers in Johannesburg - Hungwe, Chipo (Catalactica Association, 2021)
With the worsening political and socio-economic climate of Zimbabwe, migration to South Africa continues unabated. Research has already proven that migration is a result of many push and pull factors. The prospect to improve one’s life and that of one’s kin remains a key motivation for migration. What needs to be clearly articulated, in so far as Zimbabwean migration to South Africa is concerned, is the level of economic stability of Zimbabwean workers within the South African job market. This is the aspect addressed in this article, which contends that most of the Zimbabwean migrant workers in Johannesburg, South Africa are employed in career-less and unstable jobs that are precarious. While precariousness exists everywhere, and in varying levels, I argue that the migrant status is a devalued identity that leads to exclusion from certain basic rights at work and worsens the situation for most unskilled and semi-skilled Zimbabweans. Zimbabwean workers possess certain characteristics that both create advantages and disadvantages for them as they interact with employers. Employers know this fully well and capitalise on these characteristics, especially the lack of documentation needed to work and stay in South Africa.